2013
DOI: 10.1371/journal.pntd.0002380
|View full text |Cite
|
Sign up to set email alerts
|

Helminthic Infections Rates and Malaria in HIV-Infected Pregnant Women on Anti-Retroviral Therapy in Rwanda

Abstract: BackgroundWithin sub-Saharan Africa, helminth and malaria infections cause considerable morbidity in HIV-positive pregnant women and their offspring. Helminth infections are also associated with a higher risk of mother-to-child HIV transmission. The aim of this study was to determine the prevalence of, and the protective and risk factors for helminth and malaria infections in pregnant HIV-positive Rwandan women receiving anti-retroviral therapy (ART).Methodology and principle findingsPregnant females (n = 980)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…Reminder is done through phone calls, as well as home-based care approach, in order to enhance adherence to ARV drugs and other medications including co-trimoxazole prophylaxis. A similar study conducted in Rwanda reported that HIV-infected pregnant women benefit from continuous health education alongside hygiene intervention on malaria prevention during pregnancy 33. This study also reported that emphasis on co-trimoxazole prophylaxis during pregnancy is key to enhance the adherence to co-trimoxazole prophylaxis.…”
Section: Discussionmentioning
confidence: 57%
“…Reminder is done through phone calls, as well as home-based care approach, in order to enhance adherence to ARV drugs and other medications including co-trimoxazole prophylaxis. A similar study conducted in Rwanda reported that HIV-infected pregnant women benefit from continuous health education alongside hygiene intervention on malaria prevention during pregnancy 33. This study also reported that emphasis on co-trimoxazole prophylaxis during pregnancy is key to enhance the adherence to co-trimoxazole prophylaxis.…”
Section: Discussionmentioning
confidence: 57%
“…An HIV infection increases the risk of malaria by impairing the immune response, thus decreasing the ability to withstand malaria infection (Verhoeff et al, 1999), and by reducing the drug's efficacy (González et al, 2012). High malaria prevalence rates among HIV positive pregnant women were also confirmed in Rwanda (Ladner et al, 2002), particularly in urban areas (Ivan et al, 2012(Ivan et al, , 2013.…”
Section: Biological Susceptibilitymentioning
confidence: 79%
“…Ivan et al reported 6.6% co-infection while investigating prevalence of helminth and malaria infections in pregnant HIV-positive Rwandan women receiving anti-retroviral therapy (ART) [45]. The current rate was however thrice lower than that recorded by Yatich et al who reported 16.6% [12].…”
Section: Discussionmentioning
confidence: 99%